EXPLOITATION AND MANAGEMENT OF FOREST RESOURCES BY LOCAL PEOPLE IN MYANMAR: THE CASE OF PALE TOWNSHIP, SAGAING REGION - Thi Thu Ha, Tran; Mom Khin, Ei (Journal of Forestry Science and Technology, 2021)
The purpose of this study is to assess the forest resources exploitation and management of local people in Pale Township, Sagaing Region, Myanmar. Data were collected through structured questionnaire survey, focus group discussion and key informant interviews. 211 households were selected randomly from eight villages located inside reserved forests and outside reserved forests. These data were analyzed using descriptive statistics, frequency tables, percentages, Chi-square test (cross-tabulation). The results indicate that 78.2% of the respondents’ households rely on the forest resources for both subsistence needs and sale. But only 15.6% depends on forest resources as their main income source. Household characteristics such as education level, household size and main income sources are influencing the forest resources exploitation. Households inside the reserved forests received more forest income than the households outside reserved forest. Age, education and size of the household did not significantly influence the forest income. Meanwhile, gender and knowledge about sustainable forest management are the factors that influence the participation of local people in forest management. Mitigation measures such as access to higher education, alternative income generation opportunities, reduction of household size, fuel-wood substitutes, awareness raising program for participation, community forestry that empowers local communities in forest management were suggested to be enable the realization of the goal of sustainable forest management.